Exploring Localized Muscle Fatigue Responses at Current Upper-Extremity Ergonomics Threshold Limit Values. (March 2022) - Abdel-Malek, Daniel M.; Foley, Ryan C. A.; Wakeely, Fahima; Graham, Jeffrey D.; La Delfa, Nicholas J.
Objective: The purpose of this study was to evaluate localized muscle fatigue responses at three upper-extremity ergonomics threshold limit value (TLV) duty cycles. Background: Recently, a TLV equation was published to help mitigate excessive development of localized muscle fatigue in repetitive upper limb tasks. This equation predicts acceptable levels of maximal voluntary contraction (% MVC) for a given duty cycle (DC). Experimental validation of this TLV curve has not yet been reported, which can help guide utilization by practitioners. Method: Eighteen participants performed intermittent isometric elbow flexion efforts, in three separate counter-balanced sessions, at workloads defined by the American Conference of Governmental Industrial Hygenists' (ACGIH) TLV equation: low DC (20% DC, 29.6% MVC), medium DC (40% DC, 19.7% MVC), and high DC (60% DC, 13.9% MVC). Targeted localized muscle fatigue (LMF) of the biceps brachii was tracked across numerous response variables, including decline in strength (MVC), electromyography (EMG) amplitude and mean power frequency (MnPF), and several psychophysical ratings. Results: At task completion, biceps MnPF and MVC (strength) were significantly different between each TLV workload, with the high DC condition eliciting the largest declines in MnPF and MVC. Conclusion: Findings demonstrate that working at different DCs along the ACGIH TLV curve may not be equivalent in preventing excessive LMF. Higher DC workloads elicited a greater LMF response across several response variables. Application: High DC work of the upper extremity should be avoided to mitigate excess LMF development. Current TLVs for repetitive upper-extremity work may overestimate acceptable relative contraction thresholds, particularly at higher duty cycles.